Implementasi Real Time pada Pergerakan Robot Quadruped mengggunakan Multisensor dan RTOS - Hendriawan Dwi Saputro; Rizal Maulana; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Technological developments in robotics experience rapid development continuously, one of them the development of robot control systems such as increased program execution speed and better processor performance allows the use of Real Time Operating System (RTOS) in embedded systems. Improved performance is required by the robot so that the robot can reach the target of precision in moving and speed time execution. By the development of RTOS application in this research, it will apply RTOS in embedded system that is movement of quadruped robot. The RTOS used in this study is FreeRTOS because the system is already available in the Arduino microcontroller. For the RTOS type, it is a soft realtime operating system which tolerates when the robot does not match the execution time. RTOS in the system will be applied to the data retrieval of sensors and data processing for decision making. The robot in this study has a four-foot motion tool or can be called a quadruped robot composed of components HC-SR04, Arduino Mega 2560, OpenCM9.04 and OpenCM485 and servo AX-12. From the results of the study, robots have pretty good precision in moving when applying Real Time Operating System.